Parallel Processing of Forward-backward Time-stepping Method for Time Domain Inverse Scattering - Kismet, Hong Ping; Moriyama, Toshifumi; Yamaguchi, Yuji; Tanaka, Toshiyuki; Takenaka, Takashi (Progress In Electromagnetics Research (PIER), 2008)
Parallel computing is applied to FBTS method, which is one of the solution methods of time domain inverse scattering problem, to shorten the calculation time. A cluster of 8 PCs is constructed and parallel processing is realized using MPI. A 3-D reconstruction of wooden hollow cylinder from the experimental data is examined by parallel FBTS algorithm. It is shown that the parallel processing reduces the calculation time and FBTS algorithm provides proper reconstructed profiles of target with respect to relative permittivity and conductivity.